Serum and plasma hormonal concentrations are sensitive to periods of intensity and volume of soccer training - da Silva, A. S. R.; Papoti, M.; Santhiago, V.; Pauli, J. R.; Gobatto, C. A. (Science & Sports, 2011)
Objectives: To investigate the effects of a 12-week training program on the hormonal concentrations and physiological performances of soccer players. Equipment and methods: Eighteen subjects were evaluated at the beginning (T1), in the middle (T2) and at the end (T3) of the season. They had their blood collected for the analysis of cortisol, testosterone, testosterone/cortisol ratio, epinephrine and norepinephrine. The lactic and alactic anaerobic parameters and the anaerobic threshold were used as measures of physiological performance. Results: While cortisol levels were higher in T2 and T3 compared to T1 (P <= 0.05), the testosterone values and the testosterone/cortisol ratios were significantly lower in T2 and T3 compared to T1 (P <= 0.05). Norepinephrine concentrations increased from T1 to T2 and T3 (P <= 0.05). In addition, while the alactic anaerobic performance parameters decreased significantly in T2 and T3 compared to T1 (P <= 0.05), the anaerobic threshold increased in T2 and T3 in comparison with T1 (P <= 0.05). In summary, we verified that NE levels might be used as sensitive markers for variations of volume and intensity of training. In addition, the changes in the levels of the selected hormones measured in the current study were not associated to negative responses of the physiological performances.